The Long Journey of a Language: From Malay to Bahasa Indonesia - Dipa Nugraha (Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The historical narrative of Bahasa Indonesia in the books used in Indonesian universities and academic articles usually highlights three things only: the Malay language as lingua franca in Nusantara archipelago, the establishment of Balai Pustaka, and the Youth Pledge of 1928. Some important milestones may have been overlooked. This article offers a revised narrative of the history of Indonesian through its journey from a lingua franca in the Indonesian archipelago in the past to the formation of the modern Indonesian state, from Malay to Indonesian. Literature review is used in this article by involving various relevant data sources, both printed and digital, regarding the history of Bahasa Indonesia. Literature review produces several findings from the historical phase of Bahasa Indonesia. In addition, this literature review also reveals that Bahasa Indonesia finally became the national language of Indonesia after winning the competition with other languages in the Dutch East Indies. In the process, this involves the construction of identity and the struggle for power in the name of Indonesian nationalism.